Respon Pertumbuhan Dan Hasil Bawang Merah (Allium Ascalonicum L.) Terhadap Inokulasi Fungi Mikoriza Arbuskula (FMA) Dan Pupuk Limbah Baglog - Asad, Faisal Al; Dwimartina, Fina; Laila, Fadhillah (Universitas Wiralodra, 2023)
Shallots are one of Indonesia's leading horticultural commodities. Domestic demand for shallots for this commodity is very high in line with population growth. On the other hand, shallot cultivation is generally carried out with high production inputs such as the unwise use of inorganic fertilizers. This will have an impact on the decline in soil quality and will ultimately reduce production. One way that can be done to overcome this is the use of organic fertilizers such as arbuscular mycorrhizal fungi (FMA) and baglog waste fertilizer. The experimental design used in this study was a two-factor Randomized Block Design (RAK). The first factor is the dose of AMF, which consists of: M0 = 0 gr, M1 = 5 gr, and M2 = 10 gr. The second factor is the dose of baglog waste fertilizer, which consists of: B0 = 0 tons/ha, B1 = 5 tons/ha, and B2 = 10 tons/ha. The results showed: inoculation of AMF and baglog waste fertilizer had not been able to increase the growth of shallot plants, inoculation of 10 g of AMF could increase the number of tubers/clump by 21.53% compared to control, and the combination of treatment without AMF and without baglog waste fertilizer resulted in fresh weight of tubers/clump. the best clump, which is 106.68 gr.